REPRESENTASI NASIONALISME DALAM VIDEO KLIP “WONDERLAND INDONESIA” (E-Jurnal Medium, 2022)
This study discusses the Representation of Nationalism Video Clip "Wonderland Indonesia" by Alffy Rev. In criticizing the Representation of Nationalism in the Video Clip "Wonderland Indonesia". The researcher uses Roland Barthes' Semiotic Analysis method with a post-positivism paradigm approach within the framework of Stuart Hall's Representation theory. The results of this study indicate that in each Shot and the lyrics in the Video Clip, it shows that Nationalism is indicated by (1) Awareness of Cultural Diversity, (2) Commemorating the Service of the Nation's Heroes, and (3) Love for the Motherland. The implementation of this research is that the Producer of Alffy Rev Production is expected to be further developed into a Video Clip that is full of inspiration, creative and prioritizes quality because of its function as an inspiring medium for many people Keywords: Representation, Nationalism, Video Clip, Wonderland Indonesia, Semiotics Roland Barthes